Self-referral practice and associated factors among women who gave birth in South Gondar zone primary hospitals, Northwest Ethiopia: a cross-sectional study design - Eshetie, Ayenew; Belachew, Tadele Biresaw; Negash, Wubshet Debebe; Asmamaw, Desale Bihonegn; Muktar, Sualiha Abdulkader; Kebede, Adane (Frontiers in Public Health, 2023)
Background: Patient self-referral is when patients refer themselves to upper-level health facilities without having to see anyone else first or without being told to refer themselves by another health professional. Self-referral leads to a diminished quality of health care services. However, many women who gave birth referred themselves to hospitals without having referral sheets globally, including Ethiopia and the study area. Therefore, this study aimed to assess self-referral practice and associated factors among women who gave birth in south Gondar zone primary hospitals in Northwest Ethiopia. Methods: A cross-sectional mixed methods study was conducted among women who gave birth in south Gondar zone primary hospitals from June 1 to July 15, 2022. Semi-structured questionnaires were used to gather quantitative data from 561 participants who were selected by a systematic random sampling technique. Interview guides were used to collect qualitative data from selected six key informants. Quantitative data were entered into Epi Data version 4.6.0.4 and then exported to the statistical software SPSS version 25 for further analysis. Thematic analysis using open code version 4.02 software was applied for qualitative data analysis. Binary logistic regression analysis was employed. In bivariable analysis p-value less than 0.25 was used to select candidate variables for multivariable analysis. P-values less than 0.05 and a 95% confidence interval were used to determine significant variables on the outcome of interest. Results: The overall magnitude of self-referral was 45.6%, with 95% CI (41.5%, 49.9%). Had no ANC follow-up (AOR = 3.02, 95%CI: 1.64-5.57) and 1-3 ANC follow-up (AOR = 1.57, 95%CI: 1.03-2.41), poor knowledge about referral system (AOR = 4.04, 95%CI: 2.30-7.09), and use of public transportation (AOR = 2.34, 95%CI: 1.43-3.82) were significantly associated with self-referral practice. Conclusions: This study showed that nearly half of the deliveries were self-referred. ANC follow-up, women’s knowledge of the referral system, and mode of transportation were factors significantly associated with the self-referral practice. Therefore, developing awareness-creation strategies and increasing coverage of ANC 4 and above are necessary interventions to reduce the self-referral practice.